The twilight of the nation state : globalisation, chaos and war - Jha, Prem Shankar (Pluto Press, 2006)
'A strikingly intelligent, lucid and troubling book. ... It is essential reading.' Eric Hobsbawm'A thoughtful, well-documented, and passionately argued account. Giovanni Arrighi, Johns Hopkins University'A timely warning that globalisation is bringing about profound changes in the nation state and the international order.' Shashi Tharoor, Undersecretary General for Public Affairs of the United Nations, New YorkThis groundbreaking book offers an in-depth historical perspective on the rise of capitalism, written by one of the leading scholars of the Global South. Arguing that globalisation is generally poorly understood, Jha offers a new synthesis of political and economic theory that sheds light on the consequences of rapid industrialisation worldwide. Writing from outside the usual Western perspective, the book challenges many of the usual preconceptions about the impact of globalisation. Jha argues that capitalism has developed in four major stages. With a foreword by Eric Hobsbawm, the book provides a detailed history of the rise of capitalism from its early days through the industrial revolution until today. Examining the role of the nation state, this book presents a truly unique perspective on globalisation that will be of interest to all students of economic theory and international relations.